THE EFFECTIVENESS OF THE TEACHING AT THE RIGHT LEVEL (TARL) APPROACH ON LEARNING OUTCOMES IN THE TOPIC OF RELATIONS AND FUNCTIONS AMONG GRADE VIII STUDENTS - Edy, Christelita Chelcilia; Tumalun, Nicky Kurnia; Regar, Vivian Eleonora (Universitas Tanjungpura, 2026)
This research aimed to evaluate the effectiveness of the Teaching at the Right Level (TaRL) approach on student learning outcomes regarding relations and functions. This experimental study employed a pretest-posttest control group design at State Junior High School 5 Manado. The experimental class was taught using the TaRL approach, while the control class received Direct Instruction. Results indicated that the average learning outcomes of the experimental class (81.80) significantly outperformed the control class (71.48). Hypothesis testing via t-test yielded tcount = 3.619 > ttabel = 2.011 at a significance level of 0.05, confirming significant difference. Furthermore, TaRL met all effectiveness criteria: 1) the average score exceeded the learning objective attainment threshold (KKTP) of 75;2) classical mastery was achieved; 3) student responses to the learning process were positive. In conclusion, the TaRL approach is effective in improving student learning outcomes for relations and functions material among eighth-grade students.